2020
DOI: 10.1101/2020.04.01.20048496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disinfecting handheld electronic devices with UV-C in a healthcare setting

Abstract: Handheld Electronic Devices (HEDs) play a central role in the current hospital environment. However, HEDs can be a potential vehicle for transmitting (pathogenic) microorganisms. We conducted a study to assess whether disinfection with UV-C light is successful in disinfecting three different handheld electronic devices in a clinical operational setting. More than half of the baseline measurements were moderately (>10CFU) or highly (>50 CFU) contaminated. Post-disinfection the CFU was 0 in 87% of measure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After use of the sanitizer, 82 percent of the smartphones had 0 colony‐forming units. These results indicate that using the sanitizer once or twice a day can result in consistently decreased contamination of smartphones 1 …”
Section: Ultraviolet Lightmentioning
confidence: 70%
See 1 more Smart Citation
“…After use of the sanitizer, 82 percent of the smartphones had 0 colony‐forming units. These results indicate that using the sanitizer once or twice a day can result in consistently decreased contamination of smartphones 1 …”
Section: Ultraviolet Lightmentioning
confidence: 70%
“…Mobile devices, such as phones and tablets, are convenient tools to aid health care delivery; 1 however, they have been shown to carry pathogens, including Staphylococcus aureus , coagulase‐negative Staphylococcus, Micrococcus species, Pseudomonas species, and Escherichia coli , and are sources of cross‐contamination in ORs and intensive care and inpatient units 2 . Although proper cleaning and disinfection of mobile devices is essential for safe patient care, 1 one study identified that only 13 percent of health care personnel routinely disinfect them 3 . According to James Davis, MSN, RN, HEM, CIC, CCRN‐K, FAPIC, manager of infection prevention and control services, ECRI, Plymouth Meeting, Pennsylvania, contamination of mobile devices is an underrecognized concern.…”
mentioning
confidence: 99%